2013
DOI: 10.1186/2041-1480-4-9
|View full text |Cite
|
Sign up to set email alerts
|

Semantic querying of relational data for clinical intelligence: a semantic web services-based approach

Abstract: BackgroundClinical Intelligence, as a research and engineering discipline, is dedicated to the development of tools for data analysis for the purposes of clinical research, surveillance, and effective health care management. Self-service ad hoc querying of clinical data is one desirable type of functionality. Since most of the data are currently stored in relational or similar form, ad hoc querying is problematic as it requires specialised technical skills and the knowledge of particular data schemas.ResultsA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Although we showed these queries as possible as simple, they might be typically verbose and difficult to write. It is conceivable that using Allen’s temporal predicates such as "before," "after," and "during" in the pattern matching of the query [ 14 ] is useful to avoid the SPARQL filter-based comparison of the time. In order to do that, an interval-based temporal information should be given to the comparable events and they should be connected according to their relationships when the RDF data are created.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we showed these queries as possible as simple, they might be typically verbose and difficult to write. It is conceivable that using Allen’s temporal predicates such as "before," "after," and "during" in the pattern matching of the query [ 14 ] is useful to avoid the SPARQL filter-based comparison of the time. In order to do that, an interval-based temporal information should be given to the comparable events and they should be connected according to their relationships when the RDF data are created.…”
Section: Discussionmentioning
confidence: 99%
“…Assélé et al [ 13 ] developed a framework to perform SPARQL Protocol and RDF Query Language (SPARQL) queries on clinical databases to obtain results about antibiotic resistance and compared their approach with existing business intelligence approaches in terms of usability and functionality. Riazanov et al [ 14 ] developed an ontology for the clinical domain and reported that SPARQL queries can be expressed and executed in an ad hoc manner by mapping the developed clinical domain ontology and clinical data. Pathak et al [ 15 , 16 ] used publicly available life science data resources as Linked Data and searched over EMR databases integrated with these resources through SPARQL federation queries.…”
Section: Introductionmentioning
confidence: 99%
“…SADI services consume and produce RDF instances of OWL classes where the input data are decorated until they become an instance of the output OWL class. The services are deployed in a registry and can be automatically discovered, orchestrated, and invoked to return data in RDF on the query clients SHARE [ 29 ] and HYDRA [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ontology-based queries When the data is stored on a structured relational database, semantic searches can be applied for answering different kinds of RQs [ 13 ]. The PONTE platform [ 14 ] enables querying on a global EHR ontology using SPARQL statements [ 15 ].…”
Section: Introductionmentioning
confidence: 99%